Electrically conductive PDMS-grafted CNTs-reinforced silicone elastomer. (3rd May 2018) - Kong, Junhua; Tong, Yuejin; Sun, Jiaotong; Wei, Yuefan; Thitsartarn, Warintorn; Jayven, Chee Chuan Yeo; Muiruri, Joseph Kinyanjui; Wong, Siew Yee; He, Chaobin
Abstract: Conductive liquid silicone rubber-based composites were prepared through incorporation of fumed silica (FSiO2 ) and polydimethylsiloxanes (PDMS) modified MWCNTs (P-MWCNTs), and their mechanical and electrical properties were investigated. It is shown that the introduction of P-MWCNTs with P-MWCNTs/FSiO2 ratio of 0.25/30 (w/w) increases the cross-linking density and the thermal stability of the composites significantly. The improved mechanical performance, e.g., 60 % increase for Young's modulus and 47 % increase for tear strength, should be ascribed to the stronger interfacial interaction between P-MWCNTs and PDMS matrix and better dispersion of P-MWCNTs due to existence of PDMS on CNTs surface. Moreover, the better dispersion of P-MWCNTs also ensures much higher electrical conductivity than original carboxyl functionalized MWCNTs (COOH-MWCNTs) at relatively low loading, e.g., 10 −3  S m −1 versus 10 −8  S m −1 at MWCNTs/FSiO2 ratio of 2.5/30, which could be attributed to the formation of CNTs network.